Behaving Badly: Critiquing the Discourses of “Children” and Their (Mis)Behaviours - Janzen, Melanie; Schwartz, Karen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
Discourses of children as deficient and deviant are common within the education system and shape the ways in which educators interact with and respond to children. To illustrate this, we conducted a critical discourse analysis of a provincial policy document that directs schools in the development of Codes of Conduct. Drawing on poststructural theory, we demonstrate the ways in which the discourses within policy construct and reify particular identities of the child and of misbehaviour and how these discourse influence conceptions of behaviour “management.” We argue for a reconceptualization of the identity of the child as a contextualized and socially embedded being. In doing so, we articulate an opening for ethical engagements with children that rely on our responsibility for the other.